Presentation is loading. Please wait.

Presentation is loading. Please wait.

Logarithmic Equations Solving Logarithmic Equations.

Similar presentations


Presentation on theme: "Logarithmic Equations Solving Logarithmic Equations."— Presentation transcript:

1 Logarithmic Equations Solving Logarithmic Equations

2 8/15/2013 Logarithmic Equations 2 Solving Equations Solve 1. log 3 x = –3 With definition: Solution set: 27 1 = x With inverse function: 3 log 3 x = 3 – = x 3 –3 = x 27 1 { } log 3 x = –3 Exponentiate: Apply Definition:

3 8/15/2013 Logarithmic Equations 3 Solving Equations Solve 2. = x 6  4 log 36 This is already solved for x, so simplify 6 1/4 6 2x = 4 1 = 2x 8 1 = x Solution set: { } 8 1 By definition the logarithm (i.e. x) is the power of the base that yields 6  4 6  4 36 x = WHY ?

4 8/15/2013 Logarithmic Equations 4 Solving Equations Solve 3. x log x 5 = x4x4 =  x  4  x4x4 4  5 = –x, for x < 0 By definition: log a x = b iffi a b = x x 4 = 5 5 = x 4 By inverse function: x  5 4 = Exponentiate: Apply Definition: x, for x > 0 = log x 5 = 4

5 8/15/2013 Logarithmic Equations 5 Solving Equations Solve 3. log x 5 = 4 Solution set: { }  5 4 x  5 4 = 4  5 –x, for x < 0 x, for x > 0 = Question: Note: why doesn’t x 4 = 5 yield x =   5 4 ? then log x 5 is defined x  5 – = If with a negative base !! Since x 2 = 5 yields x =   5 2 then OR

6 8/15/2013 Logarithmic Equations 6 Solving Equations Solve 4. 3 log 3 (x 2 + 5) By definition: ( 2 is the power of 3 that yields x ) 3 2 = x = x 2 { ± 2 } Solution set: = x 2 ± 2 = ± x log 3 (x 2 + 5) = 2 x 2 = 4  4 ± = x By inverse function: = 3 2 = x = x  4 =  x2x2 Exponentiate:

7 8/15/2013 Logarithmic Equations 7 Solving Equations Solve 5. = x Question: Now, how do we find log 4 12 ? log 4 12 = log 4 (4 x ) To remove a variable from an exponent, find the logarithm of the exponential form 12 = 4 x

8 8/15/2013 Logarithmic Equations 8 Solving Equations Remember: a x and log a x are inverses 1. To remove a variable from an exponent, find the logarithm of the exponential form 2. To remove a variable from a logarithm, exponentiate

9 8/15/2013 Logarithmic Equations 9 One-to-One Property Review Since a x and log a x are 1-1 then 1. If x = y then a x = a y 2. If a x = a y then x = y 3. If x = y then log a x = log a y 4. If log a x = log a y then x = y These facts can be used to solve equations

10 8/15/2013 Logarithmic Equations 10 Solving Equations: Examples 6. Solve Solution set: { 1, 3 } Apply zero product rule x 2x 2 7 = 7 4x – 3 Since the exponential function is 1-1 then x 2 = 4x – 3 x 2 – 4x + 3 = 0 (x – 1)(x – 3) = 0 x – 1 = 0 OR x – 3 = 0 x = 1ORx = 3

11 8/15/2013 Logarithmic Equations 11 Solving Equations: Examples 6. Solve Solution set: { 1, 3 } x 2x 2 7 = 7 4x – 3 NOTE: x 2x 2 7 log 7 = 7 4x–3 log 7 Question: Could we use log or ln instead of log 7 ? x 2 = 4x – 3 x 2 – 4x + 3 = 0 (x – 3)(x – 1) = 0 Could have applied inverse function x = 1, 3

12 8/15/2013 Logarithmic Equations 12 Solving Equations: Examples 7. Solve 5 ln x = 10 By definition 2 is the power of the base that yields x Solution set: { ~ } x = e 2 ≈ ( ) 2 ≈ ln x = 2 Thus

13 8/15/2013 Logarithmic Equations 13 Solving Equations: Examples 8. Solution set: { –2 } Solve log 3 (1 – x) = 1 By definition: Thus 3 1 = 1 – x x = 1 – 3 = –2

14 8/15/2013 Logarithmic Equations 14 Solving Equations: Examples 9. Solve ln (x 2 – 4) – ln (x + 2) = ln (3 – x) ln x 2 – 4 x + 2 ( ) = ln (3 – x) x 2 – 4 x + 2 = 3 – x = 3x – x – 2x Using the quotient rule Since the logarithm function is 1-1, then x 2 – 4 = (x + 2)(3 – x)

15 8/15/2013 Logarithmic Equations 15 Solving Equations: Examples 9. Solve ln (x 2 – 4) – ln (x + 2) = ln (3 – x) = 3x – x – 2x = (2x – 5)(x + 2) x 2 – 4 2x 2 – x – 10 = 0 2x – 5 = 0 x = 5/2 Question: What are the domain and range of the ln function ? Solution set: { 5/2 } Why not –2 ? ORx + 2 = 0 x = –2 OR

16 8/15/2013 Logarithmic Equations 16  Quotient Example  10. Solve for x : Solving Equations log (x + 3) log (x + 1) = 2 log (x + 3) log (x + 1) = 2 = 2 x + 3 = (x + 1) 2 0 = x 2 + x – 2 = x 2 + 2x+ 1 = (x + 2)(x – 1) Solution set: { –2, 1 } WHY?

17 8/15/2013 Logarithmic Equations 17 Think about it !


Download ppt "Logarithmic Equations Solving Logarithmic Equations."

Similar presentations


Ads by Google